An emerging, less explored Subcutaneous onlay laparoscopic approach for ventral hernias with concomitant diastasis recti - Ketan Mehta; Rajesh G V; Girish Parmar; Viraj Mehta; Nirav Bavarva; Keval Charniya; Jeet Vaghasiya; Dhiren Buch; Kushal Kapashi (Scientific Reports)
Abstract Ventral Hernia (VH) is a common issue in patients with Diastasis Recti (DR). VH with concomitant DR presents a challenging scenario for surgical repair due to complexity of abdominal wall defects. Traditional open surgical procedure is associated with prolonged discomfort and poor cosmesis and resultant patients’ unacceptability. Minimal access surgery such as Sub Cutaneous Onlay Laparoscopic Approach (SCOLA), offers innovative solution in addressing both hernia defects and DR comprehensively and circumvent drawbacks of open surgery. In this prospective observational study, 33 patients with VH and DR underwent SCOLA in a tertiary care hospital in Jamnagar, India over a period of 15 months. Reconstruction of abdominal wall was done by suturing hernia defect, plication of DR and onlay polypropylene mesh augmentation by using this technique. No recurrence was detected at follow up from 4 to 18 month. Overall patient satisfaction rate was 90.9%. We conclude that, the SCOLA is a promising advancement in the treatment of patients of VH with DR with many benefits.